Adsorption Of No3--N And Po43--P in Aqueous Solution Using Granular Activated Charcoal (Gac) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
In this study, adsorption of NO3- -N and PO43--P on granular activated charcoal (GAC) was investigated depending on pH, agitation time, GAC dosage, adsorption capacity and adsorption isotherms by employing batch adsorption type. The GAC was characterized by thermogravimetric analysis (TG-DTA), scanning electron micrograph coupled with energy-dispersive X-ray spectroscopy (SEM-EDX) and BET surface area analyzer. The GAC exhibited nearly similar adsorption equilibrium time. Both NO3--N and PO43—P appeared to approach equilibrium after approximately 4 h of agitation time. In the adsorption equilibrium, the removal efficiencies of NO3- -N and PO43--P were found to be 14.6-66.0 % and 52.4-99.0 %, respectively. The adsorption data for NO3--N and PO43--P was correlated to Freundlich and Langmuir isotherm model and the equilibrium data was fitted well to the Langmuir isotherm model due to their higher correlation coefficient (R2) value. The Langmuir adsorption capacity was 1.54 and 2.56 mg g-1 for NO3--N and PO43--P, respectively, which suggests that the GAC is a good adsorbent for removal of NO3--N and PO43—P from water.